2000
DOI: 10.1677/joe.0.1670137
|View full text |Cite
|
Sign up to set email alerts
|

Neurohypophysial hormone receptors and second messengers in trout hepatocytes

Abstract: Neurohypophysial hormone receptors and second messengers were studied in trout (Oncorhynchus mykiss) hepatocytes. Arginine vasotocin (AVT) and isotocin (IT) elicited a concentration-dependent inhibition of cAMP accumulation in the presence of 5 10 -8 M glucagon (maximal effect for 4·5 10 -7 M and 1·4 10 -7 M, half-maximal effect for 2·1 10 -8 M and 0·7 10 -8 M, AVT and IT respectively). The effect of glucagon was inhibited up to 90% by AVT and 80% by IT. While AVT inhibited (up to 50%) the basal cAMP productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Activation of either pathway may lead to the phosphorylation and activation of the apical chloride channels. However, it has been suggested that AVT inhibits adenylate cyclase activity in trout and eel gill cells in suspension (Guibbolini & Lahlou, 1987 b ; Guibbolini et al 1988; Sainsbury & Balment, 1991) via the G i protein (Guibbolini & Lahlou, 1992) and in lamprey kidney tubules and trout hepatocytes (Lahlou et al 1988; Guibbolini et al 1994). Therefore, the present AVT stimulatory effect on I sc is unlikely to be mediated by an AVT‐dependent cAMP increase via V 2 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of either pathway may lead to the phosphorylation and activation of the apical chloride channels. However, it has been suggested that AVT inhibits adenylate cyclase activity in trout and eel gill cells in suspension (Guibbolini & Lahlou, 1987 b ; Guibbolini et al 1988; Sainsbury & Balment, 1991) via the G i protein (Guibbolini & Lahlou, 1992) and in lamprey kidney tubules and trout hepatocytes (Lahlou et al 1988; Guibbolini et al 1994). Therefore, the present AVT stimulatory effect on I sc is unlikely to be mediated by an AVT‐dependent cAMP increase via V 2 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have utilized this approach in amphibians (Larcher et al 1992, Butlen et al 1993) and fishes (Pang & Furspan 1984, Guibbolini & Lahlou 1990, Uchiyama & Murakami 1994, Pierson et al 1996, Guibbolini et al 2000. The present study is the first attempt to characterize pharmacologically the neurohypophysial peptide receptors in the gill respiratory cells of a marine fish.…”
Section: Pharmacological Characterization Of Receptorsmentioning
confidence: 93%
“…The presence of these receptors in a variety of tissues, such as the brain, liver, gills and head kidney, has previously been demonstrated while assessing the effects of AVT and IT administration or even analysing its mRNA expression (e.g. Motais and Maetz, 1967;Henderson and Wales, 1974;Guibbolini et al, 1988;Guibbolini et al, 2000;Amer and Brown, 1995;Conklin et al, 1996;Konno et al, 2009;Konno et al, 2010;Lema, 2010;Martos-Sitcha et al, 2014a), suggesting that physiological processes within these tissues are regulated by the vasotocinergic and/or isotocinergic systems. Interestingly, our results …”
Section: Expression Of the Avt And It Receptor Genes Following Cortismentioning
confidence: 96%